Advanced Path Integral Algorithm of Transmission Loss Allocation Using Smoothness of Loss Sensitivity - Moon, Young-Hyun; Yun, Kwang-Hee; Joo, Won; Yang, Byung Mo (IFAC-PapersOnLine, 2015)
This paper presents an advanced path-integral algorithm to determine bus-wise transmission loss allocation using smooth properties of loss sensitivities. The properties of loss sensitivity have been investigated with typical system trajectories in consideration of the market-operating strategy. The smoothness of the loss sensitivity is extensively examined along the integral paths to verify that all paths of straight line segment keep the smoothness of loss sensitivity well. The previous study has shown that, given an integral path, accurate loss allocations can be obtained by the path integral method, however, the integration procedure may require excessive computational burden for large power systems. This paper proposes an advanced loss allocation algorithm to drastically reduce the computational burden by using the smooth property of the loss sensitivity.